Thermal Property of Granite in Deep Strata and Its Effect on Thermal Zone of Surrounding Rock - Peng Xiang; Hui-Ci Xu; Hong-Guang Ji; Qi Li; Huan Wang (Shock and Vibration)
In order to clarify the changes in the thermophysical properties of rocks in deep high-temperature strata and their influence on the temperature field of the surrounding rocks, thermal property tests were conducted on rock samples taken from 1,500 to 2,000 m depth in the Xiling well construction area of Sanshandao gold mine. According to the difference equation based on the principle of heat balance, the numerical solution of unsteady heat conduction of surrounding rock can be deduced. In addition, we can explore the dynamic process of the heat-regulating ring that under ventilation measures in deep high geothermal strata and analyze its influence on the dynamic process based on the equation. The result of the research shows that the thermal conductivity of rock is mainly determined by the mineral composition and is influenced by factors such as mesostructure. Calcite and muscovite of granite have a great impact on lithology, even they just account for a relatively small percent. As the ground temperature increases step by step, the variation of the thermal conductivity of rock is less and the thermal diffusion coefficient of rock and its ability to transmit temperature changes both decrease. On the contrary, as the specific heat capacity of rock increases, its heat storage capability enhanced. Therefore, the expansion range of the heat-regulating ring of surrounding rock is influenced by mineral composition and the temperature of the environment, and the influence of the former is much greater than the latter.